Comparison of Sine-Fit Algorithms for Real Signals - Orhan, Recep; Serbes, Ahmet (IEEE, 2018)
Sine-fit algorithms for real signals have many application areas including frequency, harmonics and amplitude estimation in power grids, ADC and DAC characterization. There are numerous methods for the estimation of parameters of sinusoidal signals, due to importance. This paper compares the performance of two outstanding algorithms, in which one of them is implemented in the time domain and the other in the frequency domain. Time domain algorithm is the well-known multi-harmonic sine-fit and frequency domain algorithm is the windowed IpDFT method. Performances of these algorithms are compared, advantages and disadvantages of the methods will be given.
Keywords: sine-fit; multitone sinusoids; frequency; amplitude; phase; offset estimation; Cramer Rao lower bound; FREQUENCY ESTIMATION; LEAST-SQUARES; Engineering; Telecommunications